U.S. Equity Investment in Foreign Markets: Portfolio Rebalancing or Return Chasing? - Bohn, Henning; Tesar, Linda L. (American Economic Review, 2016)
1995). Our research examines whether the expansion of U.S. investment in foreign equities and the change in the composition of the foreign portfolio over time is consistent with standard models of international portfolio choice. To answer this question, we combine data on cross-border transactions in foreign equities with data on equity returns. Our approach has three important advantages over previous tests of models of international portfolio choice. First, we bring data on asset prices as well as data on the quantities of assets purchased to bear in the empirical tests.' Second, our testing procedure is robust to time-invariant hedge factors. This is because net purchases reflect changes in portfolio weights, and constant hedge factors that might explain home bias in levels do not affect the adjustment of the port